Tuning the functionality of a carbon nanofiber-Pt-RuO2 system from charge storage to electrocatalysis - Balan, Beena K.; Kurungot, Sreekumar (Inorganic Chemistry, 2012)
Chemical-functionalization-induced switching in the property of a hybrid system composed of a hollow carbon nanofiber (CNF) and Pt and RuO2 nanoparticles from charge storage to electrocatalysis is presented. The results of this study show how important it is to have a clear understanding of the nature of surface functionalities in the processes involving dispersion of more than one component on various substrates including carbon nanomorphologies. When pristine CNF is used to decorate Pt and RuO2 nanoparticles, random dispersion occurs on the CNF surface (C-PtRuO2). This results in mainly phase-separated nanoparticles rich in RuO2 characteristics. In contrast to this, upon moving from the pristine CNF to those activated by a simple H2O2 treatment to create oxygen-containing surface functional groups, a material rich in Pt features on the surface is obtained (F-PtRuO2). This is achieved because of the preferential adsorption of RuO2 by the functionalized surface of CNF. A better affinity of the oxygen-containing functional groups on CNF toward RuO2 mobilizes relatively faster adsorption of this moiety, leading to a well-controlled segregation of Pt nanoparticles toward the surface. Further reorganization of Pt nanoparticles leads to the formation of a Pt nanosheet structure on the surface. The electrochemical properties of these materials are initially evaluated using cyclic voltammetric analysis. The cyclic voltammetric results indicate that C-PtRuO2 shows a charge storage property, a typical characteristic of hydrous RuO2, whereas F-PtRuO2 shows an oxygen reduction property, which is the characteristic feature of Pt. This clear switch in the behavior from charge storage to electrocatalysis is further confirmed by galvanostatic charge discharge and rotating-disk-electrode studies.

Tuning the performance of low-Pt polymer electrolyte membrane fuel cell electrodes derived from Fe2O3@Pt/C core-shell catalyst prepared by an in situ anchoring strategy - Dhavale, Vishal M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
A low-Pt electrode with high performance and durability characteristic has been realized for polymer electrolyte membrane fuel cell applications from a carbon-supported Fe2O3@Pt core-shell catalyst prepared by a process involving in situ surface modification-cum-anchoring strategy. The process is based on an in-house-developed methodology for generating and interlocking the core-shell nanoparticles on the surface of the carbon substrate, which undergoes functionalization in the reaction medium itself by the intervention of the reducing agent employed in the reaction. Ascorbic acid, which was used as the reducing agent in the process, played a crucial role by making use of its multifunctional activities as reducing agent, stabilizing agent, as well as capping agent in addition to its efficiency in functionalizing the carbon surface during the course of the reaction. The formation of core-shell nanostructures could be confirmed by XRD, HR-TEM, and cyclic voltammetric analysis. The oxygen reduction property and the performance during the single cell evaluations were found to be strongly influenced by the thickness of the catalyst layer owing to the ohmic contribution from the higher mass fraction of the less conductive Fe2O3 core. However, when the thickness of the catalyst layer was kept within the threshold level, Fe2O3@Pt catalyst clearly outperforms the commercial Pt/C catalyst. This benefit of the core-shell catalyst enabled it to display a maximum power density of 900 mW/cm(2) with a significantly low cathode Pt loading of 0.05 mg/cm(2). An accelerated durability assessment of the membrane electrode assembly for 10 h gave consistent performance characteristics. The study gave convincing evidence on the feasibility of using the electrodes derived from the core-shell catalyst prepared by the in situ anchoring strategy for developing cost competitive systems and miniature cells for niche applications.

Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction

Template assisted synthesis of Ni,N co-doped porous carbon from Ni incorporated ZIF-8 frameworks for electrocatalytic oxygen reduction reaction - Priya K., Vaishna; Thomas, Minju; Illathvalappil, Rajith; K., Shijina; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2020)
A heteroatom doped porous carbon electrocatalyst with enhanced oxygen reduction reaction (ORR) performance in alkaline medium was obtained by high temperature treatment of Ni incorporated ZIF-8 frameworks and its composite with g-C(3)N(4)as a supporting matrix template. The morphology and porosity of this heteroatom containing carbon were tuned by varying the Ni : Zn molar ratio in Ni/Zn ZIF-8 and Ni/Zn ZIF-8@g-C(3)N(4)composites. The template aided synthetic strategy using g-C(3)N(4)helped in the controlled decomposition of composites leading to a heteroporous sheet like architecture with increased nitrogen content. The Ni/Zn ZIF-8 sample on heat treatment in the 800-1000 degrees C temperature range led to the formation of Ni,N co-doped porous carbon (Ni-NPC) with Ni-C active sites. The defective sites induced by nickel carbide along with the distributed N atoms on the carbon surface enabled active O(2)adsorption sites. The high surface area, high degree of graphitisation as well as the defects created by well dispersed N and Ni on porous carbon matrices favoured charge separation leading to higher electrochemical ORR activity. The Ni,N co-doped carbon catalyst in alkaline medium exhibited a limiting current density of 5.2 mA cm(-2)with a half-wave potential of 0.76 Vvs.RHE in 0.1 M KOH. The catalyst also showed improved methanol tolerance and better stability compared to the standard Pt/C catalyst.

Toward pH independent oxygen reduction reaction by polydopamine derived 3D interconnected, iron carbide embedded graphitic carbon - Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2021)
Recent advancements on the development of nonprecious electrocatalysts with iron (Fe) incorporated active centers have generated confidence on realizing cost-effective proton exchange membrane fuel cells (PEMFCs). However, most of these catalysts that emerged as a substitution for the platinum supported on carbon (Pt/C) catalysts in oxygen reduction reaction (ORR) are active under basic conditions, and their feasibility in PEMFCs remains as a challenge. In this scenario, this work reports the synthesis of a Pt-free oxygen reduction electrocatalyst prepared by the annealing of polydopamine grown melamine foam. The prepared catalyst has a three-dimensional (3D) interconnected bilayer network structure possessing the carbon nitride backbone wrapped by graphitic carbon layer bearing iron carbides and nitrides as the active centers (3DFePDC). Interestingly, the 3D-FePDC catalyst displayed an ORR activity both under acidic and basic conditions. Whereas the ORR performance of 3D-FePDC closely matches that of the commercial Pt/C in the basic medium, it displays only a low overpotential value of 60 mV under acidic conditions compared to its Pt counterpart. The kinetics of ORR on 3DFePDC is found to be similar to the four-electron (4e) reduction pathway displayed by Pt/C. Testing of a PEMFC in a single cell mode by using 3D-FePDC as the cathode catalyst and Nafion membrane delivered a maximum power density of 278 mW cm(-2), which is a promising value expected from a system based on the nonprecious metal cathode. Ultimately, as a cost-effective catalyst that can effectively perform irrespective of the pH conditions, 3D-FePDC offers significant prospects in the areas like fuel cells and metal-air batteries which work in acidic and/or basic conditions.
Keywords: acidic medium; electrocatalyst; fuel cell; graphitic carbon; Iron carbide; nitrogen doping; nonprecious metal; oxygen reduction reaction

Tailored synthesis of ultra-stable Au@Pd nanoflowers with enhanced catalytic properties using cellulose nanocrystals - Hakkeem, Hasna M. Abdul; Babu, Aswathy; Shilpa, Nagaraju; Venugopal, Adithya A.; Mohamed, A. P.; Kurungot, Sreekumar; Pillai, Saju (Carbohydrate Polymers, 2022)
A green strategy for the synthesis of bimetallic core-shell Au@Pd nanoflowers (NFs) employing banana pseudostem-derived TEMPO-oxidized cellulose nanocrystals (TCNC) as both capping and shape-directing agent via seed-mediated method is presented. Flower-like nanostructures of Au@Pd bound to TEMPO-oxidized cellulose nanocrystals (TCNC-Au@Pd) were decorated on amino-functionalized graphene (NH2-RGO) without losing their unique structure, allowing them to be deployed as an efficient, reusable and a green alternative heterogeneous catalyst. The decisive role of TCNC in the structural metamorphosis of nanoparticle morphology were inferred from the structural and morphology analyses. According to our study, the presence of -OH rich TCNC appears to play a pivotal role in the structured evolution of intricate nanostructure morphology. The feasibility of the bio-supported catalyst has been investigated in two concurrently prevalent model catalytic reactions, namely the oxygen reduction reaction (ORR) and the reduction of 4-nitrophenol, the best model reactions in fuel cell and industrial catalytic applications, respectively.
Keywords: Au@Pd; catalysis; Cellulose nanocrystals; Nanoflowers; oxygen reduction reaction

Tuning of oxygen reduction pathways through structural variation in transition metal-doped Ba2In2O5 - Thundiyil, Shibin; Pandikassala, Ajmal; Kurungot, Sreekumar; Devi, R. Nandini (ChemElectroChem, 2022)
Abstract Oxygen reduction reaction (ORR) can take place either through a two-electron pathway to form H2O2 or through a four-electron pathway to form H2O. Both the reactions are important in the respective fields, viz., H2O2 production as well as fuel cell technology, and rational design of catalysts is mandatory to acquire high energy efficiency in both cases. Here, we report the structure-electrochemical property correlation of a series of perovskite related brownmillerite compounds, Ba2In0.75M0.25O5 (M=Mn/Fe/Co/Ni/Cu), synthesized by solid-state method. On transition metal doping, octahedral distortions were observed, and the highly disordered material tends to follow the 4e transfer mechanism. More symmetrical structures followed the 2e pathway to form H2O2 as the product with high peroxide selectivity. The distortion in the octahedral arrangement can be a descriptor to finetune the selectivity of the catalysts towards the 2e and 4e pathways of ORR.
Keywords: brownmillerite; Descriptors; Electrochemical H2O2 synthesis; Octahedral distortion; oxygen reduction reaction

Tunable, amine-functionalized porous silica catalyst for CO2 transformation into cyclic organic carbonates at atmospheric pressure - Gorai, Twinkle; Thanasekar, Chandragopal; Kumar, Pawan; Babu, Athira; Kurungot, Sreekumar; Vinod, C. P. (Chemistry-A European Journal, 2025)
A silica catalyst with characteristic features of broad pore size distribution, large pore width and tunable basic sites was synthesized by a one-step green co-condensation synthesis method analogous to SBA-15 synthesis. The surface chemical features of the above catalyst were explored by XPS, N-2 and CO2 adsorption and desorption experiments. The catalyst showed 90% conversion of styrene oxide (SO) with nearly complete selectivity toward styrene carbonate (SC) in 7 hours under a solvent-free condition at a temperature of 120 degrees C with the aid of co-catalyst tetrabutylammonium bromide (TBAB). Moreover, the catalyst demonstrates versatility with various epoxide substrates, providing valuable insights into the cycloaddition reaction under ambient pressure conditions involving carbon dioxide. The mechanistic details of the catalytic conversion were investigated by the in-situ DRIFT studies and reported here.
Keywords: CO2 fixation; cyclic organic carbonates; heterogeneous catalysis; in-situ FTIR